2017
DOI: 10.1177/0363546517741135
|View full text |Cite
|
Sign up to set email alerts
|

Use of Platelet-Rich Plasma Immediately After an Injury Did Not Improve Ligament Healing, and Increasing Platelet Concentrations Was Detrimental in an In Vivo Animal Model

Abstract: The current practice of treating knee ligament injuries with PRP may not improve healing at low doses of PRP. The decreased mechanical properties and histological appearance of the torn MCL suggest that high doses of PRP decrease the quality of repair tissue. Further in vivo studies are necessary to determine the dosing and timing of PRP administration after a ligament injury before the widespread use of PRP to treat ligament injuries is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…12 Nevertheless, it seems that stimulation has some limitations. In a rabbit model, LaPrade et al 22 illustrated negative biomechanical effects for higher PRP concentrations with respect to maximum load and stiffness of treated medial collateral ligament injuries. Moreover, in equine chondrocytes, a potential ceiling effect of PRP concentration with anti-inflammatory and anabolic characteristics could be seen.…”
Section: Discussionmentioning
confidence: 99%
“…12 Nevertheless, it seems that stimulation has some limitations. In a rabbit model, LaPrade et al 22 illustrated negative biomechanical effects for higher PRP concentrations with respect to maximum load and stiffness of treated medial collateral ligament injuries. Moreover, in equine chondrocytes, a potential ceiling effect of PRP concentration with anti-inflammatory and anabolic characteristics could be seen.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,29 However, the biological value of PRP in the management of acute ligament injuries has been recently challenged. 24 To date, there have been no large comparative studies evaluating the nonoperative treatment of UCL injuries with or without PRP in only professional baseball players.…”
mentioning
confidence: 99%
“…14,15 However, it has been recently reported that increased platelet concentration beyond the physiological level did not improve functional graft healing in anterior cruciate ligament 16 and medial collateral ligament animal models. 17 Another controversial topic is the concentration of leukocytes. This study used leukocyte-poor PRP, which has been previously reported to produce more consistent results intra-articularly.…”
Section: See Related Article On Page 106mentioning
confidence: 99%